A post‐GWAS confirming GPAT3 gene associated with pig growth and a significant SNP influencing its promoter activity. (9th June 2017) - Wang, Kejun; Liu, Yufang; Xu, Qiao; Liu, Chengkun; Wang, Jve; Ding, Cui; Fang, Meiying
Summary: Our previous genome‐wide association study revealed that a SNP, ASGA0040372, located upstream of glycerol‐3‐phosphate acyltransferase 3 ( GPAT3 ), is related to growth traits in Duroc pigs. In this study, we aimed to extensively investigate the genetic variation of GPAT3 and to further verify the contribution of ASGA0040372 to growth traits and its effect on promoter activity. Our data, obtained based on gene cloning and rapid amplification of cDNA ends experiments, showed that there are 14 exons and three alternative splicing variants. Five SNPs were detected, including ASGA0040372 and four novel SNPs. Furthermore, the five SNPs obtained were used to confirm their genetic effects on pig growth by an association study in a Duroc pig population. The results indicated that three SNPs ( ASGA0040372, RS331766122 and RS346215414 ) are highly associated with average daily gain or days to 100 kg traits ( P ‐value < 0.05). Subsequent analysis suggested that the promoter region of GPAT3 gene, from –950 to –500 bp, exhibited the highest activity. We also observed that ASGA0040372 (A/G) alleles have significantly different effects on promoter transcriptional activities, which leads to differential expression of GPAT3 . Taken together, we conclude that the GPAT3 gene is associated with pig growth and that ASGA0040372 influences promoter activity of GPAT3 in pig.